Free vibrations and supersonic flutter of multilayered laminated cylindrical panels. (15th August 2020) - Muc, Aleksander; Flis, Justyna
Abstract: In the present paper the problems of optimal design of multilayered composite structures subjected to free vibration and supersonic flutter constraints are discussed. The analysis is carried out for laminated flat plates and cylindrical panels with rectangular plan form. The solutions are derived with the aid of analytical and finite element formulations. A special attention is focused on the formulation of fundamental relations for panels with the use of the approximate Donnell-Mushtari-Vlasov shallow shell theory. The structures with different boundary conditions, geometrical parameters, angle-ply fibre orientations, discrete stacking sequences and air flow directions are considered. For discrete fibre orientations a new form of design variables (reduced to four only) is proposed and employed successfully in the optimal design. Both for flat plates and cylindrical panels the maximal values of aerodynamic pressures are obtained for angle-ply laminates, and not for discrete 0°2, ±45°, 90°2 (an even number of layers of the same thickness and mechanical properties) stacking sequences.